SMAD2 linker phosphorylation impacts overall survival, proliferation, TGFβ1-dependent gene expression and pluripotency-related proteins in NSCLC - Nitschkowski, Dörte; Vierbuchen, Tim; Heine, Holger; Behrends, Jochen; Reiling, Norbert; Reck, Martin; Rabe, Klaus F.; Kugler, Christian; Ammerpohl, Ole; Drömann, Daniel; Muley, Thomas; Kriegsmann, Mark; et al. (British journal of cancer, 2025)
BACKGROUND: We investigated the impact of SMAD2 linker phosphorylation (pSMAD2L) on overall and disease-free survival, signal transduction, as well as cancer-related processes in non-small cell lung cancer (NSCLC). - METHODS: We generated A549 cells constitutively lacking pSMAD2L (A549Lsub) to gain mechanistic insights and stimulated NSCLC cell lines with inhibitors against cell cycle-associated kinases or TGFβ1. In addition, we analysed SMAD2 and pSMAD2L in alveolar epithelial cells type 2 from tumour-free lung tissue as well as in benign and malignant T cells by Western blotting. Furthermore, pSMAD2L-positive tumours and immune cells were analysed in an NSCLC patient cohort (n = 316) using multiplex immunoﬂuorescence. - RESULTS: In NSCLC cell lines and benign T cells, pSMAD2L was expressed in a mitosis-dependent manner. Loss of pSMAD2L (A549Lsub) had an anti-proliferative effect, slowed migration, and increased alternatively spliced short SMAD2 (SMAD2ΔE3). The gene signature in A549Lsub was associated with developmental and morphogenetic processes and redirected canonical TGFβ1dependent signalling. By contrast, SMAD2ΔE3 was absent in benign T cells but present in malignant T lymphoblasts. NSCLC patients with low pSMAD2L+ tumour cell density had a poorer prognosis, whereas low pSMAD2L+ immune cell density favoured overall and disease-free survival. - CONCLUSIONS: pSMAD2L antagonises anti-proliferative canonical TGFβ-signalling in NSCLC and redirects TGFβ1-dependent gene expression, whereas loss of pSMAD2L enhances SMAD2ΔE3 and affects pluripotency-associated proteins in vitro. In NSCLC patients, pSMAD2L cell density inﬂuences disease-free and overall survival in a spatially distinct manner.
Gesehen am 20.10.2025